Assessing the drinking status of liver transplant patients with alcoholic liver disease. Issue 4 (17th March 2013) - Allen, John P.; Wurst, Friedrich M.; Thon, Natasha; Litten, Raye Z.
<x xml:space="preserve">Abstract</x> The accurate assessment of drinking by patients with alcoholic liver disease is important both before and after liver transplantation. Unfortunately, self‐reports by these individuals often underestimate their actual alcohol consumption. Several recently developed biochemical measures can provide additional information on a patient's use of alcohol. This article describes ethyl glucuronide, ethyl sulfate, phosphatidyl ethanol, and carbohydrate‐deficient transferrin as biomarkers of drinking and summarizes research dealing with their application in patients with alcohol use disorders who are candidates for or recipients of liver transplantation. The article also offers suggestions for enhancing the reliability of self‐report measures of drinking status. Liver Transpl 19:369–376, 2013. © 2013 AASLD.